Blastic plasmacytoid dendritic cell neoplasm: a Swiss case series of a very rare disease and a structured review of the literature (Swiss Medical Weekly, 2025)
INTRODUCTION: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a very rare disease, with unique diagnostic challenges and often dismal outcome. There are no widely accepted treatment guidelines available. Lymphoma-like regimens with or without autologous or allogenic transplantation were the cornerstone of most therapeutic concepts. A few years ago, the CD123-directed immunoconjugate tagraxofusp emerged as a new valuable treatment option. The goal of our research was to collect available data on BPDCN-patients treated at large centres in Switzerland and worldwide and to draw conclusions regarding the incidence, clinical presentation, prognostic factors and therapeutic strategies.METHODS: We collected data from BPDCN patients from leading Swiss haemato-oncology centres from 2005 to 2022. Furthermore, we reviewed and analysed the published literature (cohorts and case reports in peer-reviewed journals) from 1997 to 2020 (structured review of the literature).RESULTS: We identified 115 international publications including 600 patients from all over the world. Most of them had very small sample sizes (only ten papers with more than ten patients) and all but one were retrospective or observational respectively. Most included patients were Europeans (n = 385, 64%) and Asians (n = 120, 20%), followed by Americans (n = 90, 15%) and patients from Australia/New Zealand (n = 3) and Africa (n = 2). BPDCN was more common in men with a predominance of 3:1. The median age (n = 414) at diagnosis was 66.5 years ranging from one month to 103 years. Newly diagnosed women were significantly younger than men (median: 62 vs 67 years, mean: 53.4 vs 59.3 years, p = 0.027) and less often had bone marrow infiltration and affected lymph nodes. Upfront allogenic transplantation as well as ALL regimens performed best, with response to first-line therapy clearly associated with better overall survival. The Swiss cohort contained 26 patients (23 males and 3 females) over 18 years (2005–2022). The median age at diagnosis was 68.5 years (range: 20–83). Ten patients underwent upfront stem cell transplantation (seven allogenic and three autologous), at least trending towards a better overall survival than other therapies. With a follow-up of 8 years, the median overall survival was 1.2 years. Eight patients in this cohort were treated with tagraxofusp, which became available in 2020 and was approved by Swissmedic in 2023.CONCLUSIONS: Our study confirms that BPDCN is a very rare and difficult-to-treat disease. Underdiagnosis and underreporting in the literature pose further challenges. Symptoms at presentation seem to differ slightly between sexes and reaching a complete remission after first-line treatment remains crucial for a prolonged overall survival. Effective treatment protocols in first line include transplantation regimens (mainly allogenic, potentially also autologous) as well as ALL protocols. In order to understand the significance of tagraxofusp as a bridge to transplant or as a continuous monotherapy in elderly patients, further evaluation with longer follow-up periods is required. In general, analysis of the Swiss patients confirmed the results from the worldwide cohort.